2020
DOI: 10.3390/biology9090289
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Central Nervous System Irradiation of Caenorhabditis elegans Induces a Limited Effect on Motility

Abstract: To clarify the tissue responsible for a biological function, that function can be experimentally perturbed by an external stimulus, such as radiation. Radiation can be precisely and finely administered and any subsequent change in function examined. To investigate the involvement of the central nervous system (CNS) in Caenorhabditis elegans’ locomotion, we irradiated a limited 20-µm-diameter area of the CNS with a single dose and evaluated the resulting effects on motility. However, whether irradiated area (be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 43 publications
(105 reference statements)
0
15
1
Order By: Relevance
“…Another study by Suzuki et al presents evidence of the CNS's activity in reducing the mortality in adult hermaphrodite C. elegans due to acute irradiation. Research shows that decreased mortality after irradiation of the CNS depends on the dose, and the body muscle around the CNS is also partly involved in reducing the mortality [73]. A device that makes the researcher able to partially irradiate C. elegans has recently been developed by Funayama et al [74].…”
Section: Effect On Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study by Suzuki et al presents evidence of the CNS's activity in reducing the mortality in adult hermaphrodite C. elegans due to acute irradiation. Research shows that decreased mortality after irradiation of the CNS depends on the dose, and the body muscle around the CNS is also partly involved in reducing the mortality [73]. A device that makes the researcher able to partially irradiate C. elegans has recently been developed by Funayama et al [74].…”
Section: Effect On Agingmentioning
confidence: 99%
“…Maremonti et al, 2019 [89] Targeted micro bream (12C ion particles) 0, 500, 100, and 1500 Gy The decrease in mortality depends on the dose due to central nervous system (CNS) targeted irradiation and may partly be due to body-wall muscle cells around the CNS. Suzuki et al, 2020 [73] Targeted micro bream (12C ion particles) 500 Gy Targeted heavy ion microbeam smaller than 10 µm. The preparation and irradiation method for the device is provided.…”
Section: Effect On Dna Responsementioning
confidence: 99%
“…Previous studies reported that the locomotion of adult worms was reduced by 1420 Gy of γ-ray irradiation [19] or 1 kGy of carbon-ion beam irradiation [17]. However, little is known about the effects of higher doses on locomotion.…”
Section: Motility Was Reduced By Whole-body Irradiation With High-dose γ-Rays and Carbon-ion Beamsmentioning
confidence: 99%
“…Body bends (head bends for 20 s) were significantly reduced when the whole body was irradiated with 0.5 kGy of carbon ions [19]. Irradiation with 1 kGy of carbon beams reduced the locomotion [15,18,19]. In this manner, non-dividing and dividing cells are different in their radiosensitivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation